Overcoming collaborative and agonistic approaches to planning: ways for its radicalization through subversive actions - Randolph, Rainer (Pontifícia Universidade Católica de São Paulo, 2019)
The article aims to identify conditions under which an “emancipating” planning may be possible as proposed by collaborative and agonistic approaches. In a brief presentation of the two forms, it is concluded that they do not fulfill their promise, in the sense that they are not able to face neoliberalization and globalization as the two preeminent characteristics of the current social order. We argue that only more radical forms of planning could have this potential insofar as they manage to articulate “subversive forces” that are always present in people’s daily lives. Thus, the last part of the work is dedicated to the indication of a more radical perspective of social actions and, especially, their subversive forms (of anti-value in the Marxian sense of “Gegenwert”).